Prove that x² - 1 is divisible by a where 8 is odd positive number. Do the solution in stepwise.

1
by Deleted account
x^2 -1 is divisible by 8, if x is an odd positive integer.

2015-04-07T20:06:03+05:30

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Let x be an integer.
x² -1 = (x - 1) (x + 1)

let  x be an odd positive integer.  x - 1  is an even positive integer or 0 = 2 k (say)
so x + 1 is then an even positive number = 2 k + 2
x² - 1 =  4 k (k + 1)

Now k and k + 1  are consecutive integers.  Hence one of them is divisible by 2.  If k is even then k+1 is an odd number.  If k is an odd number, then  k+1  is an even number.
Hence,  the product k (k+1) = 2 * [k/2] * (k+1)  or    k * [ (k+1)/2 ] * 2

thus  x² -1 =  8 * (k/2) * (k+1)    or  8 * k * [(k+1)/2]

Hence,    x² - 1  is divisible by 8.
====================================
you can use the method of proof by induction.

x² - 1  is divisible by  8  if x = 1 .

let x² - 1  be divisible by 8  for some x.  Now let us see for the next off number  x+2.
(x+2)² - 1
=  x² + 4x + 4 - 1
=  (x² - 1) + 4 (x + 1)
as x is an odd number,  x +1 is an even number.  Hence 4 (x+1) is divisible by 8.
Since both terms on RHS are divisible by 8.,  then the (x+2)² - 1 is divisible by 8.

Hence, proved by mathematical induction method.

the essence or summary of the proof is same , when you use the lemma of Euclid. Only thing is to use the language and symbols used in the lemma.
p | a means that p divides a.
Euclid's lemma says that p | a*b, then p | a or p | b or p | a*b.
ALternately, if p |a, then p| ab. --- (5)
Also, we can say that p | a/b, then pb | a. --- (6)
Let x = 2 m + 1, as any odd integer is expressed in this manner. m is an integer >= 0.
x² - 1 = (2 m + 1)² - 1 = 4 m (m + 1) --- (1)
m(m-1) = (x² - 1)/4 = an integer ---- (2)
We know that 2 | m (m+1), as one of m and m+1 is an even integer. They are consecutive integers. that is,
either 2 | m or 2 | (m+1) , hence, as per the Lemma - (5), 2 | m * (m+1)
m(m+1) | (x²-1)/4 --- (3)
Since, 2 | m(m+1) => 2 | (x² - 1)/4
=> 8 | (x²-1) by using -- (6)
hence, the proof is done.